Assessment of Designers’ Perception of Post Conflict Housing Schemes for Internally Displaced Persons (Construction Economics and Building, 2018)
With millions of internally displaced persons (IDPs) around the world, there is need to implement durable housing solutions post-conflict, that involves sustainable integration and sustainable reintegration using long term shelter programmes in the rural and urban areas. The study aims to assess designers’ assessment of post conflict housing schemes (PCHS) for internally displaced persons. Using a cross-sectional survey, the study utilized a questionnaire instrument distributed to one hundred (100) design professionals that have cognate field experience in the design, construction and management of post-conflict housing schemes. Statistical tools of bar chart, principal component analysis, categorical regression and one-way analysis of variance by SPSS v.21 was utilized. The study revealed that designers considered features such as external design and services, socio-cultural and space and maintenance features in the design of PCHS. Generalized factors considered in the selection of these features include demands of the household, choice/selection of building materials and population of IDPs. The study revealed that the failure of PCHS could be because of politics/partisanship, lack of international assistance/aid, need to make profit and non-involvement of IDPs in the rebuilding process, while the success of the scheme could be engendered by adequate participation of IDPs, effective monitoring mechanisms and increased government and non-governmental organizations’ (NGOs) participation. In conclusion, the study developed a framework for the design of PCHS for IDPs. The study recommended that professional designers should objectively consider the contributions and characteristics of IDPs in the design of PCHS. In addition, international bodies should increase pressure on government to increase commitment in re-settling IDPs. NGOs should not relent in their efforts.